2013
DOI: 10.1152/ajpcell.00342.2012
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular two-phase Ca2+ release and apoptosis controlled by TRP-ML1 channel activity in coronary arterial myocytes

Abstract: Activation of the death receptor Fas has been reported to produce a two-phase intracellular Ca2+ release response in coronary arterial myocytes (CAMs), which consists of local Ca2+ bursts via lysosomal transient potential receptor-mucolipin 1 (TRP-ML1) channels and consequent Ca2+ release from the sarcoplasmic reticulum (SR). The present study was designed to explore the molecular mechanism by which lysosomal Ca2+ bursts are coupled with SR Ca2+ release in mouse CAMs and to determine the functional relevance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Compared with the fusion process, very limited information is available for lysosomal membrane fission. Recent studies have shown that Ca 2ϩ release via lysosomal P2X4 activates CaM to trigger lysosome fusion (12 (17,20) or GECO-TRPML1 (21)), and lipid bilayers (25)(26)(27)(28), TRPML1 has been demonstrated to be a Ca 2ϩ -permeable channel in the lysosome. In this study, we investigated the role of TRPML1 in the regulation of lysosome size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the fusion process, very limited information is available for lysosomal membrane fission. Recent studies have shown that Ca 2ϩ release via lysosomal P2X4 activates CaM to trigger lysosome fusion (12 (17,20) or GECO-TRPML1 (21)), and lipid bilayers (25)(26)(27)(28), TRPML1 has been demonstrated to be a Ca 2ϩ -permeable channel in the lysosome. In this study, we investigated the role of TRPML1 in the regulation of lysosome size.…”
Section: Discussionmentioning
confidence: 99%
“…Transient receptor potential mucolipin 1 (TRPML1) (10,(13)(14)(15) belongs to the large family of transient receptor potential ion channels that permeates Ca 2ϩ , Na ϩ , and other cations (10,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Mutations in TRPML1 gene lead to mucolipidosis type IV (ML4) disease, which is characterized with defects in membrane trafficking in the late endocytic pathway (10,29), enlarged lysosomes (10,29), and impaired lysosome biogenesis (30 -32).…”
mentioning
confidence: 99%
“…RNA interference of TRPML1 gene was achieved by transfection of double-stranded siRNA of targeting TRPML1 (Accession number: BC118374) consisted of 5′-CAGCUUCCGGCUCCUG-3′ as we previously described (22). The scrambled small RNA (5′-AATTCTCCGAACGTGTCACGT-3′) was used as a negative control.…”
Section: Methodsmentioning
confidence: 99%
“…The scrambled small RNA (5′-AATTCTCCGAACGTGTCACGT-3′) was used as a negative control. Overexpression of TRPML1 was achieved by transfections of CASMCs with TRPML1 cDNA plasmids as described in our previous study (22, 23). Transfection of siRNA or cDNA was performed using the siLentFect Lipid Reagent or TransFectin Lipid Reagent (Bio-Rad, CA, USA) according to the manufacturer's instructions, as we described previously (24).…”
Section: Methodsmentioning
confidence: 99%
“…Teng et al was the first to report a method for isolating VSMCs from the mouse coronary circulation; however, we have amended the protocol significantly as they also isolated endothelial cells. Other labs have also used the protocol from Teng et al to isolate coronary arterial myocytes and airway smooth muscle cells 4,5 . The alterations we have incorporated will yield a population of cells highly enriched for VSMCs from the coronary circulation.…”
Section: Introductionmentioning
confidence: 99%